The Effect of Giving Dragon Fruit Juice (Hylocereus Polyrhizus) And Honey (Apis Mellifer) on Hemoglobin Levels of Pregnant Women in Bogor Regency - Fitriani, Ilda; Dewi Kurniati; Rini Kundaryati (International Journal of Midwifery and Health Sciences, 2026)
Anemia is a body condition characterized by lower than normal hemoglobin levels in the blood. Low hemoglobin levels in the blood can cause miscarriage, prolonged labor due to uterine inertia, postpartum hemorrhage, and shock. Anemia can be treated pharmacologically with iron tablets and non-pharmacologically with dragon fruit juice and honey. This study aims to determine the effect of a combination of dragon fruit juice and honey on hemoglobin levels in pregnant women in Bogor Regency, West Java Province, in the intervention and control groups. This type of research is a quantitative study with a quasi-experimental method with a one-group pretest-posttest with control group design . The sample in this study amounted to 30 pregnant women consisting of 15 people in the intervention group and 15 people in the control group. The sampling technique used was a purposive sampling technique . The research instruments consisted of observation sheets, SOPs for making dragon fruit juice and honey, SOPs for administering dragon fruit juice and honey, SOPs for checking hemoglobin, measuring cups, measuring spoons, blenders, and digital hemoglobinometers (Easy Touch GCHb). Data were analyzed using normality tests, homogeneity tests, paired t-tests, and independent t-tests. The results of the study showed that the combination of dragon fruit juice and honey had a strong influence in increasing the hemoglobin levels of pregnant women in the third trimester in Bogor Regency in 2025. Pregnant women are advised to consume dragon fruit juice and honey as a complementary therapy to help increase hemoglobin levels and prevent anemia during pregnancy.